β-amyloid and β-amyloid precursor protein synthesis and processing: effects of exercise and exercise-related injury - Zhen, Weizhe; Xing, Yanfeng; Li, Yongqin; Hao, Junhang; Kong, Linglei; Zhen, Hongjun (Frontiers in Cellular Neuroscience, 2026)
During the processing and assembly of β-amyloid precursor protein (APP), the amyloidogenic pathway represents a crucial component of Alzheimer’s disease (AD) pathogenesis. The non-amyloidogenic pathway does not generate toxic Aβ. For a long time, research has delved deeply into both pathways, elucidating numerous important details and mechanisms within these processes. Scientists and clinicians have sought to design effective therapeutic interventions based on these mechanisms. However, this endeavor has encountered numerous setbacks, resulting in no currently available drugs capable of reversing AD progression. Regarding APP processing and assembly, we are curious whether daily activities influence these processes. We focus on exercise as a daily activity, systematically exploring whether it affects APP processing and assembly and the underlying mechanisms. Furthermore, we examine alterations in APP processing and assembly in exercise-related injury disorders, summarizing and analyzing existing research. We discuss promising future research directions, aiming to contribute to preventing adverse outcomes following exercise-related injuries.